The parallel between press and political history of Ethiopia: a Survey up till 2013 - Salawu, Abiodun (Medwell Journals, 2016)
This study examines the parallel in the political and media history of Ethiopia. It begins with the assumption that political events influence the emergence, shape and character of media in Ethiopia. The chronology of political events reflects the chronology of developments in the media sphere. The nature and character of political leaders and regimes impact on the happenings in the media sphere as well as the nature and character of the media that emanate from such. Significantly, the study traces the political history of Ethiopia from the Axumite civilisation up till the current regime of the Ethiopian People Revolutionary Democratic Front (EPRDF). Certain landmarks in Ethiopian media history are mirrored against the various political developments and regimes in the country.